Pertimbangan Hukum Hakim terhadap Pelaku Tindak Pidana Pelecehan Seksual pada Anak - Kartika, Tantri; Subroto, Gatot; Awangga, Raden Arief (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
This study aims to examine the judge's legal considerations regarding perpetrators of child sexual abuse, specifically in Decision Number 989/PID.SUS/2022/PN.BDG in conjunction with Decision Number 86/PID.SUS/2022/PT.BDG involving defendant Herry Wirawan. The method used is normative legal research with a prescriptive approach through analysis of statutory regulations, legal principles, and relevant court decisions. The results show that the judge's legal considerations in issuing the decision are based on three aspects: juridical, sociological, and philosophical. The judge not only refers to written legal norms but also considers the social and psychological impact on the child victim and the purpose of sentencing, which is to provide a deterrent effect and protect the community. In the case studied, the judge imposed a life sentence and determined that restitution to the victim was borne by the state through the Ministry of Women's Empowerment and Child Protection. This decision demonstrates maximum protection for child victims while simultaneously enforcing the law firmly against the perpetrator.